2006
DOI: 10.1542/peds.2004-1773
|View full text |Cite
|
Sign up to set email alerts
|

Infants' Blood Volume in a Controlled Trial of Placental Transfusion at Preterm Delivery

Abstract: The blood volume was, on average, increased in the DCC group after at least a 30-second delay for both vaginal and cesarean deliveries. However, on average, euvolemia was not attained with the third stage management methods outlined above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
180
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(190 citation statements)
references
References 35 publications
4
180
0
1
Order By: Relevance
“…There are limited data on the hazards or benefits of delayed cord clamping in the nonvigorous infant. 146,147 Treatment Recommendation Delay in umbilical cord clamping for at least 1 minute is recommended for newborn infants not requiring resuscitation. There is insufficient evidence to support or refute a recommendation to delay cord clamping in babies requiring resuscitation.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…There are limited data on the hazards or benefits of delayed cord clamping in the nonvigorous infant. 146,147 Treatment Recommendation Delay in umbilical cord clamping for at least 1 minute is recommended for newborn infants not requiring resuscitation. There is insufficient evidence to support or refute a recommendation to delay cord clamping in babies requiring resuscitation.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…8 Because a greater number of infants undergoing DCC were delivered by VD, the lower proportion of CD in this group may have reduced the difference seen between the 2 approaches. Aladangady et al 3 Data are presented as mean 6 SD unless otherwise stated. * P , .05. a One infant had early-onset sepsis (blood culture positive at birth); otherwise, all sepsis was late onset.…”
Section: Discussionmentioning
confidence: 99%
“…2 The lack of benefit could reflect the lack of adequate placental transfusion during DCC for infants delivered by cesarean delivery (CD). [3][4][5] Three trials of DCC that stratified by mode of delivery found no difference in hematocrit levels or tagged red blood cells in infants delivered by CD. [3][4][5] The ACOG statement acknowledges that there are limited data indicating whether DCC performed during CD can improve placental transfusion.…”
Section: What This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…• отсроченная перевязка пуповины -до перевязки пуповины ребенка нужно удерживать ниже уровня плаценты в течение 30-45 с. Метод позволяет пе-ренести новорожденному 10-15 мл/кг крови, при-водит к уменьшению частоты внутрижелудочковых геморрагий и случаев сепсиса с поздним началом, улучшает показатели обмена железа, сокращает количество необходимых трансфузий, а также, возможно, благоприятно влияет на развитие нерв-ной системы [20,21]; • использование специальных устройств, например системы VIA, или приспособлений для взятия ми-крообразцов, например I-Stat, чтобы снизить объ-ем крови для лабораторных исследований. Кроме этого, следует с большой осторожностью относиться к частым лабораторным исследованиям (например, не назначать определение газов крови каждые 6 ч) и пересмотреть необходимость рутинных тестов (еженедельный полный подсчет форменных элементов крови, ежедневное определение газов крови и биохи-мических показателей).…”
unclassified